VI NHÂN GIỐNG CÂY ĐẲNG SÂM (CODONOPSIS JAVANICA) - Nguyễn Văn Kết (Tạp chí Khoa học Đại học Đà Lạt)
Root of Codonopsis javanica Blume is one of the most popular herbal medicines which support immunity and stress resistant. Organic nutrients and cytokinin play an important role during Codonopsis javanica Blume axillary shoot proliferation. In this study, we examined the effects of different types of media, sucrose concentrations, the amount of coconut milk, and BA (6-benzylamino purine) concentration on axillary shoot in vitro. The results indicated that 1/2MS media induced the best form of shoot after 30 days culture. Results also showed that the concentration of sucrose 4% (w/v) positive effect on growth of shoot. Axillary bud break was initiated most efficiently on modified 1/2MS media enriched with 0.5mg/l BA as buds multiplier is 3.70. The medium supplemented with 2mg/l Kinetin helps plants strong with buds multiplier is 3.26. These initial results as a basis for further research on Codonopsis javanica Blume to the supply of raw materials for pharmaceutical industry in short term, high yield, regardless of the nature, and reduce price.